Perception towards work-life balance and emotional intelligence - Suzila Farni, Binti Mohamad Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study was conducted to seek the perceptions of employees towards work-life balance and their emotional intelligence. A qualitative method has been used to collect data from four informants whom are employees in Majlis Daerah Samarahan, Kota Samarahan. The study managed to explore the perception towards work-life balance] Furthermore, the relation between work-life balance and emotional intelligence has been identified. There are some findings that correlate with prior researches and some new findings. In addition, the implications of this study towards the human resource field and methodology, limitations and direction for future research are discussed.